One Cell, Two Gears: Extensive Somatic Genome Plasticity Accompanies High Germline Genome Stability in Paramecium. (26th November 2021) - Catania, Francesco; Rothering, Rebecca; Vitali, Valerio
Abstract: Mutation accumulation (MA) experiments are conventionally employed to study spontaneous germline mutations. However, MA experiments can also shed light on somatic genome plasticity in a habitual and genetic drift-maximizing environment. Here, we revisit an MA experiment that uncovered extraordinary germline genome stability in Paramecium tetraurelia, a single-celled eukaryote with nuclear dimorphism. Our re-examination of isogenic P. tetraurelia MA lines propagated in nutrient-rich medium for >40 sexual cycles reveals that their polyploid somatic genome accrued hundreds of intervening DNA segments (IESs), which are normally eliminated during germline-soma differentiation. These IESs frequently occupy a fraction of the somatic DNA copies of a given locus, producing IES excision/retention polymorphisms, and preferentially fall into a class of epigenetically controlled sequences. Relative to control lines, retained IESs are flanked by stronger cis -acting signals and interrupt an excess of highly expressed coding exons. These findings suggest that P. tetraurelia 's elevated germline DNA replication fidelity is associated with pervasive somatic genome plasticity. They show that MA regimes are powerful tools for investigating the role that developmental plasticity, somatic mutations, and epimutations have in ecology and evolution.